Design Thinking as a Toolbox for Requirements Engineering Education: Lessons from the Classroom - Meireles, Maria Alcimar Costa; Rodrigues, Eriky; Steinmacher, Igor; Maldonado, Jose Carlos; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
Context: Design Thinking (DT) has gained popularity in software engineering education as a human-centered and collaborative approach to solving complex problems. In Requirements Engineering (RE), DT can complement traditional practices by offering concrete tools that support creativity, empathy, and stakeholder engagement. Goal: This paper presents a classroom experience in which DT was introduced not as a linear process, but as a toolbox of techniques that students could freely explore and apply to real-world projects involving external clients. Method: Students worked in teams on practical RE assignments, each involving a different system and real users. They applied DT techniques of their choice, supported by a curated selection guide called “Universo de Seleção,” which helped them identify and adapt methods suitable for their specific contexts. We conducted a qualitative analysis of students’ reflections gathered through reports and surveys. Results: The toolbox approach led to improved understanding of requirements elicitation, better engagement with users, and development of key skills such as teamwork and communication. Students also demonstrated autonomy and critical thinking in selecting techniques appropriate to their project contexts. Conclusion: This experience highlights the potential of using DT as a toolbox to enrich RE education, offering flexibility and encouraging deeper engagement with both technical and human aspects of requirements elicitation.